Post-cam clunk syndrome after posterior stabilized total knee arthroplasty as a sign of early femoral component loosening - Toda, Akihiko (Asia Pac J Sports Med Arthrosc Rehabil Technol, 2017)
Soft tissue impingements are well-known complications of total knee arthroplasty. The impingements usually occur between the medial or lateral femoral component and tibial insert, and between the patella and femoral components. We report a rare case of impingement of the soft tissue between the femoral intercondylar fossa and post of the polyethylene insert, which caused pain and walking disability. After the surgery for the arthroscopic removal of the soft tissue, the symptoms disappeared. However, prosthetic loosening of the femur occurred several months after the arthroscopic surgery, requiring revision surgery. We would propose to call this symptom as post-cam clunk syndrome.